Research on the multi-objective collaboration damping control strategy based on multi-resource - Zhou, Bo; Xu, Yunyang; Sun, Xinwei; Jiang, Xiaofeng (Frontiers in Energy Research, 2024)
To improve the stability margin of the power grid under unconventional conditions and enhance the fault emergency support capability of AC/DC grids, this paper investigates multi-resource and multi-objective collaboration damping control strategy method based on a multi-input multi-output (MIMO) system model, which considers the multiple control impacts. Based on the analysis of system oscillation characteristics, appropriate feedback signals and controller installation locations are selected based on the modal ratio index. to realize the control effect, the HVDC and energy storage devices are used. Finally, the coupled robust controllers based on robust mechanism are designed out. Simulation results in PSCAD software show that, compared to traditional damping controllers, the controller designed is more suitable for system conditions with large perturbations and uncertainties.